SYNTHESIS OF COMPENSATED CORIOLIS VIBRATORY GYROSCOPES - Apostolyuk, Vladislav A.; Didyk, Zinaida V. (Proceedings of National Aviation University, 2010)
Synthesis of the Coriolis vibratory gyroscopes compensation with the help of the Wiener-Kolmogorov procedure led to the proper transfer function of the optimal feedback controller is proposed in this paper. CVG as the object of compensation is considered as sensitive element transfer function, which was obtained after analysis of it’s dynamics in terms of the amplitude-phase variables. Efficiency of the obtained transfer function of the optimal feedback controller is demonstrated by means of numerical simulation.